Response Characteristics of Tunnels with Curvilinear Axes under Obliquely Incident Lateral SV Seismic Waves - Yongchao Sun; Meijing Wang; Chengjie Ai; Chuanwei Fan; Huiling Zhao (Advances in Civil Engineering)
Influenced by topography, geological conditions, and environmental factors, the alignment design of long-distance tunnels frequently incorporates curved tunnel segments. When subjected to obliquely incident transverse SV seismic waves, curved tunnels exhibit more complex patterns of stress and deformation, which could become pivotal in governing the seismic safety of the tunnel compared to their straight counterparts. This paper presents a numerical simulation on the response characteristics of curved tunnels subjected to obliquely incident lateral seismic SV waves. Curved tunnels exhibit more complex deformation under oblique SV wave incidence compared to vertical incidence, with notable increases in axial tensile deformation and shear deformation, both axially and in-plane, as the angle of incidence rises. While vertical incidence primarily induces lateral bending, oblique incidence results in bending influenced by both wave direction and incidence angle, necessitating advanced seismic design considerations for tunnel integrity. The bending moment distribution in curved tunnels under oblique incidence displays nonuniformity and localized concentration. The findings underscore the importance of considering the oblique incident angle in the design and analysis of curved tunnels for seismic safety.